2020
DOI: 10.1016/j.actatropica.2020.105452
|View full text |Cite
|
Sign up to set email alerts
|

Ross-Macdonald models: Which one should we use?

Abstract: Ross-Macdonald models are the building blocks of most vector-borne disease models. Even for the same disease, different authors use different model formulations, but a study of the dynamical consequences of assuming different hypotheses is missing. In this work we present different formulations of the basic Ross-Macdonald model together with a careful discussion of the assumptions behind each model. The most general model presented is an agent based model for which arbitrary distributions for latency and infec… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 42 publications
0
7
0
Order By: Relevance
“…In the existing literature, Simon et al 17 investigated the differences between exponential and nonexponential distributions in homogeneous models. Their findings indicated that variations in disease stage distributions have an impact on the transmission process.…”
Section: Conclusion and Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In the existing literature, Simon et al 17 investigated the differences between exponential and nonexponential distributions in homogeneous models. Their findings indicated that variations in disease stage distributions have an impact on the transmission process.…”
Section: Conclusion and Discussionmentioning
confidence: 99%
“…In the existing literature, Simon et al 17 . investigated the differences between exponential and nonexponential distributions in homogeneous models.…”
Section: Conclusion and Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Over the years, a variety of mathematical models have been developed to aid in understanding the malaria transmission mechanism, improving control strategies, and reducing the global impact of malaria. The very first malaria model was developed by Ronald Ross [3,4].…”
Section: Introductionmentioning
confidence: 99%
“…Compartmental mathematical models for vector-borne diseases are vastly found in the literature [ 31 , 32 , 33 ], and are mainly based on and inspired by the Ross–McDonald malaria model [ 34 ]. In particular, there is a significant number of articles associated with mathematical modeling of malaria dynamics [ 35 , 36 , 37 , 38 , 39 , 40 ].…”
Section: Introductionmentioning
confidence: 99%